Factors Influencing E-Filing Usage Among Indonesian Taxpayers: A Technology Acceptance Model (TAM) Theory Approach - Triwibowo, Edi; Dian Sulistyorini Wulandari; Leni Anggraini (Indonesian Journal of Economic & Management Sciences, 2024)
The research is designed to investigate the impact of perceived usefulness, tax understanding, social factors, and information technology readiness on the utilization of e-filing among individual taxpayers registered at KPP Pratama North Cikarang. The study's population comprises individual taxpayers registered at KPP Pratama North Cikarang, with a sample of 100 respondents selected through random sampling based on the Slovin formula. Employing a quantitative approach, the research gathered data by distributing questionnaires to taxpayers and employed multiple linear regression for data analysis. The findings indicate that perceived usefulness, tax understanding, social factors, and information technology readiness positively and significantly influence the adoption of e-filing. Collectively, these factors impact the use of e-filing by individual taxpayers registered at KPP Pratama North Cikarang